FLET ANIMATION IN MOTION DESIGN AS A METHOD OF INFORMATION VISUALIZATION - Хиневич, Р. В.; Довженко, І. Б.; Родіна, В. А.; Яворський, О. Л.; Ковальчук, О. В. (Art and Design, 2019)
Define the specifics of flat animation as an innovative means of visualizing information in the field of motion design. Methodology. General scientific methods of research are used: analysis and synthesis, systematization and generalization, for studying of flat animation and its specifics in motion design, determination of features of its design and composite decisions, formation of research conclusions. The method of comparative analysis of types of modern animation is applied. Results. The features of the use of flat animation in various fields of application are considered, compositional methods and tools that are used to implement a variety of design decisions are analyzed, specific graphic image methods are identified and the basic elements inherent in modern animation products are identified. Scientific novelty. The most effective methods of visualization of information in motion-design are determined, the role of flat animation in motion-design is shown, its means of expression and their influence on the readability of information are analyzed. Practical significance. Investigated and systematized the techniques and means of composite solutions flat animation for mobile applications. Features that distinguish flat animation from other animated products are defined. For the first time, a paper calendar with mobile interactivity has been developed and implemented. This opens up the possibility of creating innovative printing calendars.